2014
DOI: 10.1111/jipb.12275
|View full text |Cite
|
Sign up to set email alerts
|

Slr0151 in Synechocystis sp. PCC 6803 is required for efficient repair of photosystem II under high‐light condition

Abstract: Cyanobacteria are ancient photosynthetic prokaryotes that have adapted successfully to adverse environments including high-light irradiation. Although it is known that the repair of photodamaged photosystem II (PSII) in the organisms is a highly regulated process, our knowledge of the molecular components that regulate each step of the process is limited. We have previously identified a hypothetical protein Slr0151 in the membrane fractions of cyanobacterium Synechocystis sp. PCC 6803. Here, we report that Slr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 61 publications
4
38
0
Order By: Relevance
“…The Slr0151 protein does not have homology with protein phosphatases. It has been previously assigned to assist in regulation of the D1 de novo synthesis and photosystem II (PSII) disassembly/assembly under high light stress as well as to play an important role in the assembly of photosystem I (PSI) . Our results indicate that Slr0151 has yet another function determining the optimal ratio between phosphorylated and nonphosphorylated forms of Fd5, namely preventing its overphosphorylation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The Slr0151 protein does not have homology with protein phosphatases. It has been previously assigned to assist in regulation of the D1 de novo synthesis and photosystem II (PSII) disassembly/assembly under high light stress as well as to play an important role in the assembly of photosystem I (PSI) . Our results indicate that Slr0151 has yet another function determining the optimal ratio between phosphorylated and nonphosphorylated forms of Fd5, namely preventing its overphosphorylation.…”
Section: Discussionmentioning
confidence: 66%
“… who analysed the transcriptomics organization of the entire Synechocystis genome, and was corroborated by Yang et al . at the protein level. We observed that elimination of the SpkG kinase resulted in a significant decrease in the expression of the Slr0151 protein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether Msf1 is associated with a thylakoid membrane complex, we analyzed membrane fractions of the wild type (UVM4), the Msf1-GFP strains (Msf1-GFP14 and Msf1-GFP16), and msf1 by 2D bluenative (BN)/SDS-PAGE using a slightly modified protocol (Yang et al, 2014). The UVM4 strain was used in order to increase the expression of the chimeric Msf1-GFP protein.…”
Section: Msf1 Interacts With At Least One Component Of the Chlorophylmentioning
confidence: 99%
“…Among the mutants with the lowest FII values, msf1was chosen for subsequent characterization. 77K fluorescence emission spectra were measured using a fluorescence spectrophotometer (F-2500; Hitachi) as described (Yang et al, 2014) with slight modifications. An excitation wavelength of 435 nm (5-nm bandwidth) was used to induce chlorophyll fluorescence.…”
Section: Mutant Library Construction and Screening With Chlorophyll Fmentioning
confidence: 99%
See 1 more Smart Citation